2016
DOI: 10.1038/srep27447
|View full text |Cite
|
Sign up to set email alerts
|

DNA Demethylation Rescues the Impaired Osteogenic Differentiation Ability of Human Periodontal Ligament Stem Cells in High Glucose

Abstract: Diabetes mellitus, characterized by abnormally high blood glucose levels, gives rise to impaired bone remodeling. In response to high glucose (HG), the attenuated osteogenic differentiation capacity of human periodontal ligament stem cells (hPDLSCs) is associated with the loss of alveolar bone. Recently, DNA methylation was reported to affect osteogenic differentiation of stem cells in pathological states. However, the intrinsic mechanism linking DNA methylation to osteogenic differentiation ability in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…For a further analytical approach, the mRNA expression levels of ALP, OSX, RUNX2 and COL1 were measured by RT-qPCR. During osteogenesis, numerous osteogenic marker genes of hPDLSCs, including ALP, COL1, OSX, and RUNX2, can be increased (31). ALP, as an early-stage osteogenic-specific gene, serves an important role in bone formation and mineralization (15).…”
Section: Discussionmentioning
confidence: 99%
“…For a further analytical approach, the mRNA expression levels of ALP, OSX, RUNX2 and COL1 were measured by RT-qPCR. During osteogenesis, numerous osteogenic marker genes of hPDLSCs, including ALP, COL1, OSX, and RUNX2, can be increased (31). ALP, as an early-stage osteogenic-specific gene, serves an important role in bone formation and mineralization (15).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this suggestion, in‐vitro application of 5‐aza‐2′‐deoxycytidine to decrease DNA‐methylation levels in human periodontal ligament stem cells was capable of rescuing the osteogenic capacity of these cells under high‐glucose conditions . A subsequent animal experiment showed that diabetic rats with increased DNA‐methylation levels in their periodontal ligaments exhibited reduced bone mass and bone density . It seems that suppression of DNA methylation could enhance the osteogenic capacity of human periodontal ligament stem cells even in pathological states, such as diabetes mellitus.…”
Section: Methodsmentioning
confidence: 70%
“…DNA methylation is a critical regulator of stem cell differentiation. Interestingly, it has been described that the DNA methyltransferase inhibitor 5-aza-2 -deoxycytidine (5-aza-dC) is able to increase the stemness of periodontal ligament stem cells (PDLSCs), and also to enhance the reprogramming efficiency of human gingival mesenchymal stem cells (hGMSCs) [26,78]. Another report showed that a short pre-application of 5-aza-dC for 24 h increased the responsiveness of DPSCs to osteogenic differentiation protocols [79], a similar result to the one obtained after preconditioning DPSCs for 48 h with BIO or WNT-3A, as we showed in our own previous research [13].…”
Section: Discussionmentioning
confidence: 99%